Answer:
x =
![(-5)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jywz3lm7o7sc9ae0dmisfrm7av4tx17dks.png)
Explanation:
Step 1: Simplify both sides of the equation.
3x+4(x+3)=7
3x+(4)(x)+(4)(3)=7(Distribute)
3x+4x+12=7
(3x+4x)+(12)=7(Combine Like Terms)
7x+12=7
7x+12=7
Step 2: Subtract 12 from both sides.
7x+12−12=7−12
7x=−5
Step 3: Divide both sides by 7.
![(7x)/(7) = (-5)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/swexz824o5cf85sgwaguas833shbtc7w3m.png)